ATRIBUSI MASYARAKAT PELOSOK TERHADAP PROGRAM PEGAWAI NUSANTARA SEHAT DI DESA KAHAYYA KECAMATAN KINDANG KABUPATEN BULUKUMBA (Fakultas Dakwah dan Komunikasi, 2020)
Does this study aim to determine the attributions of remote communities to the Healthy Nusantara Employees program? And how is the interpersonal communication interaction between Nusantara Sehat employees in an effort to improve the health of remote communities in Kahayya Village, Kindang District, Bulukumba Regency? This type of research is descriptive and uses qualitative research methods and uses several informants to conduct interviews and observations. This method is used in extracting information, namely the researcher goes directly to the field to conduct observation interviews and documentation. The results showed that the role of Nusantara Sehat employees in carrying out their work programs at Kahayya Village was to act as a motivator, as a mentor for the community (facilitator), and as an educator. And the community's attribution of the Healthy Nusantara Employees program in Kahayya Village is influenced by several causes, namely: situational causes (influenced by their environment), personal influence, having women, having desires and obligations. As well as in building an interpersonal relationship, Nusantara Sehat employees use an intense approach, namely an interpersonal communication approach in the form of a trusting attitude, an open attitude, and a supportive attitude.